Student and Teacher Perception on English Language Use in Foreign-University-Affiliated Colleges in Nepal (The Harvest, 2023)
Foreign-university-affiliated colleges in Nepal offer a new dimension in education delivery with many opportunities and benefits. Students in these colleges are exposed to an international curriculum and a prospect of learning in an English language environment. On the one hand, Nepalese students can complete their higher education in Nepal and the nation could keep the tuition revenue from leaving the country. On the other hand, students from other countries could be attracted to these colleges and help boost the national GDP of Nepal. Furthermore, a better English language prospect has tremendous benefits to students in today’s connected world where Nepalese students can globally compete in terms of jobs or other professional prospects. The perception of Nepalese students and teachers on the English language use is generally positive despite many differences in terms of the factors such as urban vs. rural, private schools vs. government schools, as well as their educational background and place of origin. This paper examines the prospect of English language use in foreignuniversity- affiliated colleges in Nepal and the significance of such colleges as well as the importance of the English language to Nepal.